Courtship, marriage and marriage breakdown
1 online resource (viii, 238 pages).
Keywords: This book explores the history of marriage and marriage-like relationships across five continents from the seventeenth century to the present day. Across fourteen chapters, leading marriage scholars examine how the methodologies from the new history of emotions contribute to our understanding of marriage, seeking to uncover not only personal feeling but also the political and social implications of emotion. They highlight how marriage as an institution has been shaped not just by law and society but also by individual and community choices, desires and emotional values. Importantly, they also emphasize how the history of non-traditional and same-sex relationships and their emotions have long played an important role in determining the nature of marriage as an institution and emotional union. In doing so, this collection allows us to rethink both the past and present of marriage, destabilizing a story of a stable institution and opening it up as a site of contest, debate and feeling.